Could Artificial Intelligence be the Subject of Criminal Law? - Mahardhika, Vita; Astuti, Pudji; Mustaffa, Aminuddin (Yustisia, 2023)
The  use  of  artificial  intelligence  can  increase  productivity  and efficiency in various sectors of life. However, it can also potentially cause legal problems especially criminal law if they result in losses. The subject of law in determining who should be responsible is a separate issue. This research examines whether technology using artificial intelligence can be used as the subject of criminal law so that criminal responsibility can be held. This research is normative juridical research with a statutory, conceptual approach and cases related to artificial intelligence and criminal law issues. The study shows that the ability to analyze and make decisions possesed by artificial intelligence can be indicated as "malicious intent".  Yet, the  concept  of  punishment  for  the  artificial intelligence system  requires  a  unique  formula,  as  the  personality  of  artificial intelligence cannot be equated with the personality of a human or  legal  entity.  The  granting  of  legal  status  through  a  criminal sanction  mechanism  in  the  form  of  machine  deactivation, reprogramming, and the severity of destroying machines is expected to provide future solutions to minimize the risk of criminal acts by artificial intelligence.